2020
DOI: 10.1186/s12884-020-2852-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with short birth interval in low- and middle-income countries: a systematic review

Abstract: Background: There is ample evidence of associations between short birth interval and adverse maternal and child health outcomes, including infant and maternal mortality. Short birth interval is more common among women in low-and middle-income countries. Identifying actionable aspects of short birth interval is necessary to address the problem. To our knowledge, this is the first systematic review to systematize evidence on risk factors for short birth interval in low-and middle-income countries. Methods: A sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
81
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 36 publications
12
81
0
4
Order By: Relevance
“…Debido al poco tiempo de preparación y la urgencia de los resultados, la estrategia de búsqueda de la presente revisión no contó con la orientación de un bibliotecólogo. Sin embargo, nuestro equipo tiene experiencia en la elaboración de revisiones sistemáticas 31 - 36 . Solo se incluyeron tres bases de datos, pero cada una de ellas aporta un aspecto clave a la búsqueda: Embase está especializada en farmacología, PubMed es la base de datos médica más nutrida del mundo, y Lilacs es la base de datos latinoamericana más completa.…”
Section: Discussionunclassified
“…Debido al poco tiempo de preparación y la urgencia de los resultados, la estrategia de búsqueda de la presente revisión no contó con la orientación de un bibliotecólogo. Sin embargo, nuestro equipo tiene experiencia en la elaboración de revisiones sistemáticas 31 - 36 . Solo se incluyeron tres bases de datos, pero cada una de ellas aporta un aspecto clave a la búsqueda: Embase está especializada en farmacología, PubMed es la base de datos médica más nutrida del mundo, y Lilacs es la base de datos latinoamericana más completa.…”
Section: Discussionunclassified
“…Studies on birth interval showed that household wealth status [ 15 ], residence [ 15 ], husband education [ 16 ], maternal education [ 17 , 18 ], contraceptive use [ 19 , 20 ], media exposure [ 21 ], women health care decision making autonomy [ 22 ], religion [ 23 , 24 ], maternal occupation [ 15 ], breastfeeding duration [ 23 ], parity [ 24 ], and maternal age [ 25 ] were significant predictors of birth interval.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of kunika identified by women and men in Bauchi communities differ from those reported to be associated with short birth interval in quantitative studies in low- and middle-income countries. In a recent systematic review [ 11 ] only two factors were consistently associated with short birth interval in quantitative studies: shorter duration of breastfeeding and female sex of the previous child. The factors most frequently examined in the reviewed studies included age of the mother, education of the mother, education of the father, and household socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the south of Nigeria found that loss of traditional healthcare practices was associated with more western education [ 40 ]. However, most studies examining maternal education and birth interval have found shorter birth interval associated with less maternal education [ 11 ]. The mapping groups in Bauchi talked openly about the use of aphrodisiacs and pornography as causes of frequent sex and hence kunika .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation